Capitalism Paradigm shift in the practice of Organizational Human Resource Management - ISKANDAR, ISKANDAR (International Journal of Management Excellence (ISSN: 2292-1648), 2021)
It is not easy to change the mindset about the importance of capitalism paradigm shift in organizational human resources management that is based on dignity and humanity. Capitalism is no longer just an economic system but it has interfered the practice of human resources management in an organization. Therefore, the existence of human resources within the organization must be treated not as an ’asset’ (means of production) but as people who have ’something’. By that, the role of leader and employee that complements each other is needed in order to change this capitalism issue. Until now, the networks and relationships which are formed by capitalism not only break the economic system but also change the behavior of human resources (HR) in the organization. The effect that came up because of this change is the spirit of individuality both in consumption and production. As a result, this condition makes the collectivity and solidarity become irrational. The competition skill as to gain the most, the highest, and to consume large quantities in order to receive a status symbol is a demand to enter and survive in the life of the capitalistic system. This paper is basically examined the effort of capitalism paradigm shift in organizational human resources management. In details, the writer wants to examine: (1) The paradigmatic struggle in human resources management and (2) change capitalism paradigm to deep ecology paradigm in the practice of human resources management in the organization. From here, the writer expects that this could change the attitude and behavior in the organization. In other words, the existence of human resources within the organization is essential to be treated not as an ’asset’ (means of production) but as people who have ’something’ not as an individual that "possessed" something.